When Water Does not Flow: Elite Capture of Freshwater Canals in Bangladesh - Sarker, Mou Rani; Joshi, Deepa; Mannan, Fouzia; Rahman, M Mokhlesur (2024)
The coastal region of Bangladesh, known as the deltaic food basket, supports around 80 million people whose livelihoods rely heavily on freshwater sources like canals. Climate change and human interventions in this area significantly impact water-related challenges. Freshwater canals, drainage peripheries of large rivers, are the lifeline to water access and availability, supporting crop cultivation, livestock farming, and fish production and processing in southwestern Bangladesh. These canals are mostly under the control of local and external elites who hold long-term leases to exclusive rights and use, even though legislation in principle disallows the leasing of flowing streams of water. Following this, the study objectives are to analyze (a) power and politics to control freshwater canal, (b) gender relation and its dynamics in access, use, and control of fresh water. The study was carried out in two villages, Kultali and Dhankhali, located in the coastal area of Munshigonj union within the Shyamnagar upazila of the Satkhira district in southwestern Bangladesh, employing mixed methods. The results show legislation is subverted and flowing canals are leased out, mostly to non-locals. The leaseholders utilize social and political connection to monopolized canal systems, thereby exacerbating water scarcity. Small-scale and marginal farmers, fishers, and women are the primary victims of this canal appropriation. According to AgWISE Module about 44.44% of men and 32.46% of women experienced productive water insecurity, i.e. water issues related to adequacy, reliability, accessibility, and safety. The outcomes of canal water capture have worsened food security, dietary diversity, and economic inequalities.